THE EFFECT OF STOCK PRICES ON FINANCIAL PERFORMANCE WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE - Putu Megawati, Ida Ayu; Dewanti, Made Amanda; Nurmalasari, Made Ratih; Dewiningrat, Ayu Indira; Prawitasari, Putu Putri (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research is quantitative research with an exploratory approach, namely an approach that uses a number of previous studies as the most fundamental source as reference material for finding new novelty elements in the research being carried out. This research uses secondary data obtained from the Indonesian Stock Exchange for 10 years from 2013-2023. This data includes data on insurance companies in Indonesia. Researchers analyzed the data using the smart PLS 4.0 analysis tool. The result in this article show the Financial Performance variable can influence share prices. Researchers have an alternative perspective, namely that stock prices can actually have a positive relationship and have a significant influence on financial performance. This hypothesis can be proven and supported by the results of the first line path coefficient which shows that the stock price variable can have a positive relationship on employee performance because The P-Values value is positive and is below the 0.05 significance level, namely 0.016. This is due to logical reasons because better share prices can increase investors which makes financial performance more stable. Apart from that, the influence of share prices can be more significant on financial performance if it is supported by good corporate governance. This is also proven from the second row of the third table in this research which shows that the variable Good Corporate Governance can moderate the influence of the Stock Price variable on Financial Performance because the P-Values value has a positive direction and is below the 0.05 significance level, namely 0.000. Thus, the first and second hypotheses in this research can be accepted and proven. Keywords: Stock Price, Financial Performance, Good Corporate Governance